1987
DOI: 10.1111/j.1464-410x.1987.tb04570.x
|View full text |Cite
|
Sign up to set email alerts
|

Modified Method of Diuresis Renography for the Assessment of Equivocal Pelviureteric Junction Obstruction

Abstract: Thirty-five hydronephrotic kidneys, in which diuresis renography showed either an equivocal (13) or non-obstructive (22) response pattern, were studied by a modified method in which intravenous frusemide was given 15 min before the start of the renogram so as to assess elimination during the period of maximum diuresis. Thirteen kidneys were identified as obstructed, including three in which the standard diuretic renogram appeared to exclude obstruction. These results indicate that the modified method increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 17 publications
2
33
0
1
Order By: Relevance
“…Using the FϪ15 protocol, 10 of 13 (77%) equivocal kidneys and 3 of 22 (13%) nonobstructive kidneys demonstrated obstruction. 10 Foda et al compared 2 diuresis renography techniques (Fϩ20 and FϪ15) in 88 children and showed that the number of positive results was significantly higher with the FϪ15 protocol, although the number of equivocal results was identical for both protocols. Because none of the patients was submitted to both protocols, conclusions could not be drawn as to the superiority of FϪ15 renography in the detection of established obstruction.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Using the FϪ15 protocol, 10 of 13 (77%) equivocal kidneys and 3 of 22 (13%) nonobstructive kidneys demonstrated obstruction. 10 Foda et al compared 2 diuresis renography techniques (Fϩ20 and FϪ15) in 88 children and showed that the number of positive results was significantly higher with the FϪ15 protocol, although the number of equivocal results was identical for both protocols. Because none of the patients was submitted to both protocols, conclusions could not be drawn as to the superiority of FϪ15 renography in the detection of established obstruction.…”
Section: Discussionmentioning
confidence: 96%
“…4 -7 English et al described the FϪ15 diuretic renogram in which furosemide is injected 15 minutes before the radiotracer. 10 This protocol allows for the maximum diuretic effect to coincide with radioactivity entering the renal pelvis. They studied 35 hydronephrotic kidneys, in which standard diuresis renography showed either an equivocal (37%) or nonobstructive (63%) response pattern.…”
Section: Discussionmentioning
confidence: 99%
“…The collecting system and bladder appear in the third to fourth minute, after the activity peak ( T max ). The excretory phase presents with rapid disappearance of the tracer from the renal parenchyma and drainage through the urinary tract, in keeping with the decreasing part of the renogram ( concave line ) F-15 method (English et al 1987 ) includes the administration of furosemide 15 min before the tracer and allows the observation of the urinary tract behaviour under a maximal diuretic effect. The last method to be introduced is F + 0 (Adeyoju et al 2001 ).…”
Section: Diuretic Scintigraphymentioning
confidence: 99%
“…Quantification of diuretic response to furosemide has been studied by several groups [39][40][41]. In normal well-hydrated patients with urine flow rates of approximately 5 mL/min, the diuresis increased to 20 mL/min by 3-6 min, reaching a maximum of 24 mL/min at 15-18 min.…”
Section: Diagnosis Of Obstructionmentioning
confidence: 99%
“…Because the time course of diuretic response to furosemide during diuretic renography is not reached immediately, elimination of the tracer from the renal pelvis may be achieved before the diuresis has reached levels sufficient to demonstrate obstruction, thus yielding false negative or equivocal results. A modified protocol was developed in which furosemide was given 15 min before the start of the imaging [40]. Several studies testing this modified protocol (F 0 15) have concluded that it provides an accurate assessment of the drainage of the upper urinary tract, improves both sensitivity and specificity of the test, and, hence, is recommended in patients with equivocal results on standard (F/20) diuretic renography, especially if the obstruction is of intermittent nature [41,42] (Fig.…”
Section: Diagnosis Of Obstructionmentioning
confidence: 99%